Thin -film solar cell - THE INVENTOR HAS WAIVED THE RIGHT TO BE MENTIONED (2018)
The utility model relates to a solar cell field relates to a thin -film solar cell especially. The utility model discloses a thin -film solar cell, including the substrate to and set gradually barrierlayer, back electrode layer, p type light absorbing zone, cadmium selenide layer, sulphur zinc selenide layer and transparent conducting film on the substrate along the direction of keeping away fromthe substrate. The utility model discloses the formation of interface department interfacial state defect can be effectively prevented, thin -film solar cell's short -circuit current has been improved to thin -film solar cell's performance has been improved. 本实用新型涉及太阳能电池领域，特别地涉及种薄膜太阳能电池。本实用新型公开了种薄膜太阳能电池，包括衬底，以及沿远离衬底的方向依次设置在衬底上的阻挡层、背电极层、p型光吸收层、硒化镉层、硫硒化锌层和透明导电层。本实用新型可以有效防止界面处界面态缺陷的形成，提高了薄膜太阳能电池的短路电流，从而提高了薄膜太阳能电池的性能。